Ipsilateral ureteroureterostomy: does function of the obstructed moiety matter?. Issue 1 (February 2019) - Kawal, T.; Srinivasan, A.K.; Talwar, R.; Chu, D.I.; Long, C.; Weiss, D.; Van Batavia, J.; Kolon, T.F.; Shukla, A.R.
Summary: Purpose: Upper pole nephrectomy has been the traditional surgical management of children with poorly functioning upper pole moieties in duplex renal collecting systems having ureteral ectopia and ureterocele. However, ablative surgery confers a risk of functional loss to the remnant moiety due to vasospasm or vascular injury. It was hypothesized that ipsilateral ureteroureterostomy (IUU) is a safe and feasible approach for the management of these patients and that residual function in the obstructed upper pole does not affect surgical outcomes. Materials and methods: All patients with duplex systems who underwent IUU between 2010 and 2016 were retrospectively reviewed. Patients were sorted into two groups based on pre-operative imaging: those having <10% upper pole moiety function (UPMF) and those having ≥ 10% UPMF. Outcomes assessed were postoperative complications (Clavien–Dindo classification), need for secondary surgery, and radiological outcomes. Results: The study cohort comprised 53 children with ectopia or ureterocele affecting the upper pole in a duplex system, 21 with UPMF <10% (median function 0% and median age 1.49 years) and 32 with UPMF ≥ 10% (median function 15% and median age 0.91 years). Median follow-up was 27.4 months and 27.6 months. In both the groups, prenatal hydronephrosis was the most common presentation (57% and 56%, respectively; p = 0.18) followed by urinary tract infection. Mann–Whitney U test comparing the two groups revealed no significant differences in any of the outcomes assessed. No patient required secondary surgery. Conclusion: Ipsilateral ureteroureterostomy is a safe, definitive surgical intervention that preserves the renal architecture in children with duplex collecting systems regardless of upper pole function. Fig. 1 Bar graph showing radiological outcomes in each group. UPMF = upper pole moiety function. Fig. 1